Kajian Adaptif Vub Padi Gogo Spesifik Lokasi di Provinsi Riau - Emi Sari Ritonga; Ida Nur Istina; Usman Usman; M. Giri Wibisono (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Ritonga ES, Istina IN, Usman U, Giri Wibisono MG. 2020. Adaptive study of upland new high yielding paddy locations specific in Riau province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).New high yielding varieties (VUB) are one of the technology components that are easiest for farmers to adopt. Dissemination of VUB deployments runs relatively quickly when VUB can adapt well to an area, but not all VUB can give the same results in one particular location, including Riau. This study aims to obtain new high yielding varieties of upland rice which are adaptive in a specific site. The research was conduct in the dry land of Harapan Baru village, Mandau District, Bengkalis Regency from May to August 2020. The test used a randomized block design with five replications. The varieties used are Inpago 8, Inpago 9, Inpago 10, Inpago 11, Inpago 12 and Rindang. Parameters observed included plant height (cm), maximum number of tillers (stems), number of productive tillers (tiller), number of filled grains (grains), number of empty grains (grains), weight of 1000 grains (grams) and productivity (tonnes/ha). Data were analyzed using variance (ANOVA). If there was a difference in the 95% confidence level, the DMRT continued test performed. The results showed that Inpago 8 adapted to the environment and was able to provide the highest productivity (5.9 tonnes/ha) and gives the best preference by farmers.